Arthroscopic and 3D CT Scan Evaluation of Femoral Footprint of the Anterior Cruciate Ligament in Chronic ACL Deficient Knees - Das, Anupam; Yadav, C. S.; Gamanagatti, Shivanand; Pandey, R. M.; Mittal, Ravi (The Journal of Knee Surgery, 2019)
The outcome of single-bundle anterior cruciate ligament (ACL) reconstruction depends largely on the anatomic placement of bone tunnel. The lateral intercondylar ridge (LIR) and bifurcate ridge (BR) are useful bony landmarks for femoral tunnel placement. The purpose of our study was to compare the bony landmarks of ACL footprint on femur by three-dimensional computed tomography (3D CT) scan and arthroscopy in chronic ACL-deficient knees. Fifty patients above 18 years of age who were diagnosed of having ACL tear were selected for the study. All the cases were more than 6 months old since the injury. Preoperative 3D CT scan of the affected knee was obtained for each of them. They underwent single-bundle anatomic ACL reconstruction. Measurements were done on the preoperative 3D CT and arthroscopy to quantify the position of the LIR and BR. The proximodistal distance of lateral femoral condyle was 21.41+/−2.5 mm on CT scan and 22.02+/−2.02 mm on arthroscopy. On preoperative 3D CT scan, the midpoint of the LIR was found to be located at a mean distance of 11.17±2.11 mm from the proximal margin of the lateral femoral condyle. On arthroscopy, it was at 10.18+/−1.52 mm from the proximal margin the lateral femoral condyle. The “bifurcate ridge”(BR) was not visible in any of the cases during arthroscopy or CT scan. We concluded that LIR is an easily identifiable bony landmark on arthroscopy in all cases. It can also be identified on CT scans. BR is not identified both on arthroscopy and CT scans in chronic ACL tears. The arthroscopic measurements of bony landmarks are quite close to those of CT scan. Midpoint of LIR is at 52.185% of the proximodistal distance on CT scan evaluation and it is at 46.21% on arthroscopic evaluation.
Keywords: anatomic single-bundle reconstruction; anterior cruciate ligament; lateral intercondylar ridge; femoral tunnel